A Study of Students’ Subtitling Project on “Ambilkan Bulan” Movie - Esriaty Sega Kendenan (Langkawi: Journal of The Association for Arabic and English, 2019)
This paper aims at investigating how student subtitlers practice making subtitle of “Ambilkan Bulan” movie from Indonesian into English. This subtitling project is expected to help students sharpen their translation skills while learning linguistic and cultural aspects of both Indonesian as the source language (SL) and English as the target language (TL) in this study. In addition, students are also expected to have more practices on the technical aspects of subtitle to convey the message in the limited time and space by applying existing subtitle software. The data of this study were taken from students’ translations in Subtitling class. The data were analyzed descriptively to identify the strategy used by students based on Gottlieb's ten subtitle strategies and the technical constraints they commonly faced in making the subtitle. The results of this study indicate that students generally apply all of these strategies with varying frequencies and linguistics-related problems. Transcription strategy is the most frequent strategy applied by the students. This study also shows that students still struggle with the technical aspects related to cueing duration, rhythm, and division of subtitle which are sometimes less synchronous and eventually distracted viewers’ convenience